2014
DOI: 10.1088/1475-7516/2014/08/042
|View full text |Cite
|
Sign up to set email alerts
|

Precision growth index using the clustering of cosmic structures and growth data

Abstract: Abstract:We use the clustering properties of Luminous Red Galaxies (LRGs) and the growth rate data provided by the various galaxy surveys in order to constrain the growth index (γ) of the linear matter fluctuations. We perform a standard χ 2 -minimization procedure between theoretical expectations and data, followed by a joint likelihood analysis and we find a value of γ = 0.56 ± 0.05, perfectly consistent with the expectations of the ΛCDM model, and Ω m0 = 0.29 ± 0.01, in very good agreement with the latest P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 82 publications
4
22
0
Order By: Relevance
“…The second result is that the differences of the bias models are absorbed in the fitted value of the DM halo mass in which LRGs live, and which ranges from ∼ 6.2 × 10 12 h −1 M ⊙ − 1.2 × 10 13 h −1 M ⊙ , for the different bias models and in the case of DESY1COSMO bias. As it can also be seen from Table II, our derived mass of the host DM halo mass is consistent with that of Papageorgiou et al [61], while Sawangwit et al [62] and Pouri et al [63] found M h ≃ (1.9 − 2) × 10 13 h −1 M ⊙ . FIG.…”
Section: Constant Growth Indexsupporting
confidence: 92%
“…The second result is that the differences of the bias models are absorbed in the fitted value of the DM halo mass in which LRGs live, and which ranges from ∼ 6.2 × 10 12 h −1 M ⊙ − 1.2 × 10 13 h −1 M ⊙ , for the different bias models and in the case of DESY1COSMO bias. As it can also be seen from Table II, our derived mass of the host DM halo mass is consistent with that of Papageorgiou et al [61], while Sawangwit et al [62] and Pouri et al [63] found M h ≃ (1.9 − 2) × 10 13 h −1 M ⊙ . FIG.…”
Section: Constant Growth Indexsupporting
confidence: 92%
“…The corresponding weighted mean and the combined weighted standard deviation of the DM halo mass are: Table 3. Results of the χ 2 minimization procedure using the LRGs ACF of 2SLAQ (see Sawangwit et al 2011 and Table 1 in Pouri et al 2014). In this case we have ∆AIC ≃ 0.…”
Section: Fitting Models To the Lrgs Sdss Dr5 Acf Datamentioning
confidence: 92%
“…In the context of TRK and BPR bias models within the Planck (TT+lowP+lensing) and the DES/Planck/JLA/BAO cosmology respectively, it is interesting to mention that rescaled bias data provide an LRG host DM halo mass consistent at ∼ 2σ level with that of Sawangwit et al (2011), namely M h ≃ 2(±0.1) × 10 13 h −1 M⊙ (see also Pouri, Basilakos & Plionis et. al.…”
Section: Fitting Models To the Bias Datamentioning
confidence: 99%
“…For the ΛCDM we have γ 6/11 0.545, and one typically expects γ(0) = 0.56 ± 0.05 for ΛCDM-like models [66]. The growth index can obviously be reexpressed as…”
Section: Linear Growth and Growth Indexmentioning
confidence: 98%